Depression and anxiety are associated with high health care utilization and mortality among adults with congenital heart disease. (1st February 2019) - Benderly, Michal; Kalter-Leibovici, Ofra; Weitzman, Dahlia; Blieden, Leonard; Buber, Jonathan; Dadashev, Alexander; Mazor-Dray, Efrat; Lorber, Avraham; Nir, Amiram; Yalonetsky, Sergei; Razon, Yaron; Chodick, Gabriel; et al.
Abstract: Background: The significance of depression/anxiety among ACHD patients in terms of health care utilization is unknown and data on the association with mortality are scarce. Methods: Analyses comprised 8334 ACHD patients, age ≥ 18 years, insured by a large healthcare organization (2007–2011). Depression/anxiety were determined by diagnoses and treatments recorded in the organization database. Adjusted utilization relative rates (RRs) were estimated with negative binomial models and mortality hazard ratios (HRs) with the Cox proportional hazard model. Results: ACHD patients with depression/anxiety ( N = 2950, 35%) were more likely to be older (mean ± SD: 54 ± 17 vs. 45 ± 18 years), women (61% vs. 45%), and have comorbidities than counterparts without depression/anxiety. Following multivariable adjustment, patients with depression/anxiety had more primary care and cardiology clinic visits, more emergency department visits and more hospitalizations. RRs (95% confidence interval) were: 1.31 (1.27–1.35); 1.07 (1.01–1.13); 1.60 (1.46–1.77); and 1.18 (1.08–1.29) respectively, for diagnosis before the study period, and 1.36 (1.31–1.42); 1.22 (1.14–1.30); 1.43 (1.24–1.60) and 1.47 (1.33–1.64), respectively, for diagnosis during the study. Stratifying by age, the highest adjusted primary care and cardiology visit RRs were found among 18–24 years old patients and the lowest among patients ≥65 years. Between 2007 and 2017, 905 patients died. Depression/anxiety were associated with increased mortality risk with adjusted HRs: 1.10 (95% CI: 0.94–1.29) for past diagnosis and 1.40 (1.17–1.67) for study period depression/anxiety diagnosis. Conclusions: Depression/anxiety in ACHD patients is associated with increased health-care utilization and a higher risk of death. The efficacy of addressing patients' psychosocial needs in optimizing health-care utilization and improving prognosis needs further evaluation. Highlights: >1/3 of Adult congenital heart disease (ACHD) patients have depression or anxiety. Depression/anxiety among ACHD patients are associated with increased health care utilization. Both inpatient (hospitalizations, ER visits) and outpatient visits are increased. Primary care and cardiology visit rates are highest among young and lowest among ≥65 years patients. ACHD patients with depression/anxiety are at a higher risk of death.